EDUCATION AND EDUCATION OF CHILDREN WITH PHYSICAL AND MENTAL FAULTS IN POLISH KINDERGARTENS (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the aims and tasks of upbringing and teaching disabled children.